The Influence of Job Satisfaction, Organizational Justice, Job Involvement, and Rewards on Employee Performance at PT. Puri Global Sukses Tbk - Tresia Ambarita; Dhenny Asmarazisa; Rona Tanjung (Electronic Journal of Education, Social Economics and Technology, 2026)
This study aims to analyze the influence of job satisfaction, organizational justice, job involvement, and rewards on employee performance at PT. Puri Global Sukses Tbk. The research approach used is associative quantitative, with 40 permanent employees as respondents. Data were collected using a Likert scale questionnaire (1–5) and analyzed with SPSS version 26 through validity, reliability, classical assumptions, and multiple linear regression tests. The results showed that the four independent variables, namely job satisfaction, organizational justice, job involvement, and rewards, had a positive and significant effect on employee performance. Among these variables, job involvement had the most dominant influence on improving performance. The coefficient of determination (R²) value of 0.837 indicates that 83.7% of the variation in employee performance can be explained by the four independent variables, while the remaining 16.3% is influenced by other factors outside this study. These findings confirm that increasing job satisfaction, organizational justice, job involvement, and an effective reward system are important strategies for companies to achieve optimal employee performance.